2005
DOI: 10.1038/nrmicro1099
|View full text |Cite
|
Sign up to set email alerts
|

Poxvirus tropism

Abstract: Despite the success of the WHO-led smallpox eradication programme a quarter of a century ago, there remains considerable fear that variola virus, or other related pathogenic poxviruses such as monkeypox, could re-emerge and spread disease in the human population. Even today, we are still mostly ignorant about why most poxvirus infections of vertebrate hosts show strict species specificity, or how zoonotic poxvirus infections occur when poxviruses occasionally leap into novel host species. Poxvirus tropism at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
489
0
13

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 474 publications
(504 citation statements)
references
References 189 publications
(221 reference statements)
2
489
0
13
Order By: Relevance
“…8 Within this virus family, especially vaccinia virus, the closely related cowpox virus and the rabbit pathogen myxoma virus have been studied and found to possess genes that can interfere with cellular activation pathways, such as interferon-and TNF signalling. It is noteworthy that important host regulatory genes are even conserved in the genomes of highly attenuated vaccinia virus strains, such as modified vaccinia virus Ankara (MVA) or NYVAC, candidate strains for future vaccination protocols.…”
Section: Introductionmentioning
confidence: 99%
“…8 Within this virus family, especially vaccinia virus, the closely related cowpox virus and the rabbit pathogen myxoma virus have been studied and found to possess genes that can interfere with cellular activation pathways, such as interferon-and TNF signalling. It is noteworthy that important host regulatory genes are even conserved in the genomes of highly attenuated vaccinia virus strains, such as modified vaccinia virus Ankara (MVA) or NYVAC, candidate strains for future vaccination protocols.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these strains, deletions of host range genes that have been identified to date from MV [66] would make excellent candidates for vaccines. Studies that have selectively deleted such genes have found no reduction in their in vitro replication levels, yet a severe defect in their ability to cause disease in rabbits (Tab.…”
Section: Prevention Control and Vaccinationmentioning
confidence: 99%
“…Studies in a mouse model of glioma has shown that this virus is quite effective in infecting tumor tissue in vivo and effectively 'cured' mice from these brain tumors [56]. These studies have fostered enthusiasm in the prospect of using this virus clinically to treat human cancers [66]. In this case, special considerations will have to be met to ensure the safety of both wild and cultivated rabbit populations.…”
Section: Prevention Control and Vaccinationmentioning
confidence: 99%
“…93,94 Yet, even with the newfound ability to engineer viral genomes to produce a new generation of safer, specific oncolytics, a true therapeutic frontrunner has yet to emerge. This is likely due not to inherent problems with the viruses now in circulation, but rather to their rapid clearance by the host immune system.…”
Section: Adaptation Attenuation and Engineering: Building A Bettermentioning
confidence: 99%